Arterial hypertension and social loneliness in an older population from 55 years and older. Barquisimeto, Venezuela (Revista Venezolana de Salud Pública, 2020)
Social loneliness has been shown to be closely related to the health status of the population. The present research assessed the prevalence of arterial hypertension and its association with the perception of social loneliness in residents over 55 years of age in the Antonio Carrillo community. In this regard, an analytical prevalence study, 92 people were studied as population, the previous diagnosis of arterial hypertension was asked, blood pressure was measured, and the data collection tool ESTE II was subsequently applied. It was found that, in the population over 55 years of age, according to the general characteristics of the population, the female sex predominated (63%); in addition, the majority of the habitants were between the ages of 55 and 64 (52.2%); according to marital status, married residents prevailed (41.3%); with regard to education, the majority of the population underwent incomplete primary education (24%) and in regards of the inactivity by the unemployment situation (76.1%). 65.2 % of the population was found to be hypertensive, and in terms of the perception of social loneliness, 68.5% of the population was found to have the same conditions. As in fact, when the association between blood pressure and the perception of social loneliness was made, it was specified that 68.3% of the habitants with perception of social loneliness were hypertensive (p>0.05).
Keywords: Elderly; arterial hypertension; social loneliness; ESTE II